Cultural Approach to HIV/AIDS Harm Reduction in Muslim Countries - Hasnain Memoona (BMC, 2005)
Abstract Muslim countries, previously considered protected from HIV/AIDS due to religious and cultural norms, are facing a rapidly rising threat. Despite the evidence of an advancing epidemic, the usual response from the policy makers in Muslim countries, for protection against HIV infection, is a major focus on propagating abstention from illicit drug and sexual practices. Sexuality, considered a private matter, is a taboo topic for discussion. Harm reduction, a pragmatic approach for HIV prevention, is underutilized. The social stigma attached to HIV/AIDS, that exists in all societies is much more pronounced in Muslim cultures. This stigma prevents those at risk from coming forward for appropriate counseling, testing, and treatment, as it involves disclosure of risky practices. The purpose of this paper is to define the extent of the HIV/AIDS problem in Muslim countries, outline the major challenges to HIV/AIDS prevention and treatment, and discuss the concept of harm reduction, with a cultural approach, as a strategy to prevent further spread of the disease. Recommendations include integrating HIV prevention and treatment strategies within existing social, cultural and religious frameworks, working with religious leaders as key collaborators, and provision of appropriate healthcare resources and infrastructure for successful HIV prevention and treatment programs in Muslim countries.